MODEL HUBUNGAN INTI-PLASMA PADA INDUSTRI AKUAKULTUR TAMBAK UDANG A RELATIONSHIP MODEL OF NUCLEAR-PLASMA IN AQUACULTURE INDUSTRY OF PRAWN POND - Sukardi, Purnama; Margiwiyatno, Agus ; Rosyad, Anisur; , Tobari; Santoso, Jarot; Anwar, Nurul (Pembangunan Pedesaan, 2006)
The relationship between nuclear and plasma in aquaculture businesses as one of several agricultural businesses were observed in two regions, i.e., Lampung and West Java. CP Bahari and Triasta Citarate Ltd. were used as a sample of this relationship. The results showed that the education level of aqua-culturist was 80% senior high school and 20% secondary school. CP Bahari (nuclear) had already fulfilled the duties to the plasma aqua-culturist. However, cooperation (Bima Utama) as a channelling agent did not work properly. There was not self-help group; the only group was a neighborhood from which the company controlled aqua-culturist. Extension from Fisheries Agency Office was not properly done. Local government autonomy resulted in too many tax regulations from which overlapping taxes had been happened. Aqua-culturist cooperation (KUD) did not work as in agreement with Central Bank of Indonesia. The information of plasma credit was not clear as well as the balance position of their money. In Triasta Citarate, the existing of KUD was just to speed up the process of money transfer to the nuclear.